IMPLEMENTASI SISTEM PEMBERIAN PAKAN AYAM OTOMATIS BERBASIS IOT PADA AYAM KAMPUNG MENGGUNAKAN APLIKASI PONSEL PINTAR - imam sukarno (Politeknik Harapan Bersama Tegal, 2022)
Feeding native chickens is generally done manually so it is less effective. This automatic free range chicken feeding system is the right solution to make it easier for farmers to set the feeding schedule and the amount of free range chicken feed. Feeding was carried out according to the age data and the number of native chickens entered. The age and number of free range chickens will determine the time schedule for feeding and the amount of free range chicken feed given. The system uses Real Time Clock (RTC) as a time comparison to set the time schedule for feeding native chickens. The amount of free range chickens feed is regulated based on delay in opening the feed reservoir valve. The sytem is equipped with the concept of Internet Of Things (IOT). The data on the system will be sent to the cloud data server which is then forwarded to the smart phone application so that it can be monitored for feed availability and remote feeding status through the application on the farm manager’s smart phone as long as it is connected to the internet network. Feeding native chickens can also be done directly via the button available on the smartphone application. The results obtained are the system can provide chicken feed according to the schedule that has been set.